Marion : a novel - Rowan, Leah (St. Martin's Press, 2026)
Marion is in deep. She's stolen money from the Manhattan ad agency where she works in a desperate bid to help her sister escape an abusive marriage, but the bus breaks down before she can make it to Saratoga Springs. It's late at night, and the only place with vacancies is an old set of cabins on the outskirts of town. She pays for a room in cash, and ends up chatting with Norm, the young innkeeper who's handsome, charming and a touch hung-up on his elderly mother. Back in her room, she steps into the shower, scrubbing off the late-summer heat, when the curtain is pulled back ... Norm Billings is there with a knife. He raises his arm to strike, but before he does, Marion knees him in the balls, grabs the knife, and stabs the life out of him. Now, she's covered in blood, and she's a woman on the run-not just a thief, but a killer, too. Where will she go? How will she save both herself and her sister? And what mysteries will she uncover as she does? In Psycho, Hitchcock shocked audiences when he killed off his protagonist. But what if the leading lady had fought back? Marion offers an alternate history of the most famous dead blonde to ever grace the silver screen. Only this time, the knife is in her hands-and she's no victim.